2014
DOI: 10.1002/ijch.201400054
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Hosts Based on a Rigid 9,10‐Dihydroanthracene Scaffold for Full‐Color Electrophosphorescent Devices

Abstract: Two bipolar hosts, CzDPO and CzDOxa, comprising a hole‐transporting carbazole and an electron‐transporting diphenyl phosphine oxide or oxadiazole with a saturated linker (9,10‐dihydroanthracene) have been synthesized and characterized. The saturated linker limited the effective extension of π conjugation, leading to high triplet energies (ET=2.97–2.98 eV). The diastereomers with a rigid configuration provided an amorphous thin film with high thermal (Td=415–444 °C) and morphological stability (Tg=188–224 °C). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…To achieve bipolar hosts with high triplet energy, strategies, such as impeding electronic communication between electron-donating and electron-withdrawing moieties, have been developed. These include introducing a saturated bridging center or a highly twisted linker to minimize effective π conjugation. , Recent research has shown promising results in achieving a high external quantum efficiency for blue, green, and red PhOLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve bipolar hosts with high triplet energy, strategies, such as impeding electronic communication between electron-donating and electron-withdrawing moieties, have been developed. These include introducing a saturated bridging center or a highly twisted linker to minimize effective π conjugation. , Recent research has shown promising results in achieving a high external quantum efficiency for blue, green, and red PhOLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…The bipolar materials with donor-acceptor (D-A) system comprising π or σ bridge have engaged with great significance because of their distinctive properties like well-defined structural system, balance hole and electron transport, ease of purification along with authentic reproducibility, high luminescence quantum yield, [16][17][18] and easy fabrication of large area devices. [19][20][21][22][23][24][25][26][27] Over a wide range of tailored D-A moieties along with unique architecture system with wise selection and proper linking of donor and acceptor motifs allows to tune the photophysical, thermal, and electrochemical properties. [28] Indeed, a host material for PhO-LEDs device should possess some inherent features: (I) higher triplet energy (E T ) than the phosphorescent guest, which prevent reverse energy transfer, (II) suitable highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) for effective charge injections into the emitting layer from the adjacent charge transporting layers, (III) large HOMO-LUMO energy gap (E g ) than the phosphorescent guest, and (IV) high glass transition temperature (T g ) to provide good film morphology and avoid morphological changes at device operating voltage and so on.…”
Section: Introductionmentioning
confidence: 99%